Breaking the clean room barrier: exploring low-cost alternatives for microfluidic devices - Rodríguez, Cristian F.; Andrade-Pérez, Valentina; Vargas, María Camila; Mantilla-Orozco, Andrés; Osma, Johann F.; Reyes, Luis H.; Cruz, Juan C. (Frontiers in Bioengineering and Biotechnology, 2023)
Microfluidic devices, also known as labs-on-a-chip (LOCs), have emerged as potential instruments for optimizing operations and decreasing costs in a variety of industries, including the pharmaceutical, medical, food, and cosmetics industries. However, the high price of conventional LOCs generated in clean room facilities has increased the demand for inexpensive alternatives. Polymers, paper, and hydrogels are a few of the materials that can be utilized to create the inexpensive microfluidic devices covered in this article. In addition, we highlighted different manufacturing techniques, such as 3D printing, soft lithography, and laser plotting, that are suitable for creating LOCs. The selection of materials and fabrication techniques will depend on the specific requirements and applications of each individual LOC. This article aims to provide a comprehensive overview of the numerous alternatives for the development of low-cost LOCs to service industries such as pharmaceuticals, chemicals, food, and biomedicine.